Luxury fashion brand coolness: Niche versus mass cool - Aleem, A.; Loureiro, S. M. C.; Breazeale, M. (Spanish Journal of Marketing - ESIC, 2024)
Purpose: This study aims to analyze the relationship of mass versus niche brand coolness on consumers’ brand loyalty, mediated by attitude toward the brand and moderated by conspicuous consumption; test the moderating role of conspicuous consumption and the mediating role of attitude between mass versus niche cool brand and brand love; and analyze whether results are stable when categorizing the luxury brands as niche versus mass cool brand. Design/methodology/approach: Study 1 uses a panel sample to establish the mediating role of attitude toward the brand between perceptions of brand coolness and brand loyalty. Study 2 is an experimental survey study to describe the moderating role of conspicuous consumption on the relationship between mass/niche brand coolness and brand love and between mass/niche coolness and attitude toward the brand. Study 3 is a conjoint analysis that delineates the distinct factors that consumers attribute to mass versus niche cool brands in the luxury fashion arena. Findings: This study demonstrates that attitudes mediate the relationship between brand coolness and brand loyalty. Conspicuous consumption only moderates the relationship between brand coolness and attitudes in the case of niche cool brands. In a realistic field experiment, the authors confirm the mediating impact of attitude and the moderating influence of conspicuous consumption. The authors also attempt to provide coolness dimensions that tend to be more associated with mass luxury brands and those more related to niche luxury brands. Originality/value: These studies provide a fresh look at the concept of brand coolness, mass and niche cool brands in the context of luxury fashion brands.